FOSTERING STUDENT’S SCIENCE LITERACY AND CREATIVITY THROUGH A STEM-INTEGRATED PROJECT-BASED LEARNING MODEL - Zahra, Afida Ifanaula; Eralita, Norma (Jurnal Pendidikan Matematika dan IPA, 2026)
Scientific literacy and creativity are essential present century competencies that students must develop. The implementation of the Project-Based Learning (PjBL) model integrated with STEM is applied as a solution to foster students' scientific literacy and creativity. This research aims to explore the implementation of the STEM integrated PjBL model in optimizing scientific literacy and student creativity in the environmental pollution learning process.. The research employed a quantitative descriptive approach using a quasi-experimental method. The design used was a non-equivalent control group design, with samples selected through cluster random sampling. The instruments included pretest and postest questions to assess scientific literacy, and observation sheets to measure students’ creativity. The collected data were first tested for homogeneity and normality. Further analysis was conducted using the Independent Samples t-Test and N-Gain test. The t-test results showed a significance value of 0.000, indicating a significant difference in the mean scores between the experimental and control classes. The N-Gain test revealed that the scientific literacy improvement in the experimental class reached 0.67 (moderate category), while the control class reached 0.40 (moderate category). Meanwhile, creativity in the experimental class achieved an N-Gain score of 0.79 (high category), and the control class scored 0.58 (moderate category). Therefore, it can be summarized that the PjBL-STEM model effectively enhances the scientific literacy and creativity of seventh-grade students at SMP Negeri 33 Semarang.